2020
DOI: 10.1590/0103-6440202003870
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of a New Ready-To-Use Calcium Silicate-Based Sealer

Abstract: The aim of this study was to evaluate the antibacterial potential of a calcium silicate-based sealer (Bio-C Sealer, Angelus) against common bacteria in primary and secondary endodontic infections. Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus mutans were exposed to fresh Bio-C Sealer for 24 h by the agar diffusion method (n=5). Additionally, the antibacterial activity was investigated against E. faecalis and S. mutans biofilms (48 h old) grown in discs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
(33 reference statements)
1
13
0
7
Order By: Relevance
“…A literatura mostra que além da capacidade de induzir a biomineralização após implantação no tecido conjuntivo (Benetti, et al, 2019;Alves Silva, et al, 2020), o Bio-C Sealer tem capacidade de alcalinização atingindo pH de 10 até 21 dias (Mendes, et al, 2018;Zordan-Bronzel, et al, 2019). Sabe-se que pH superior a 9 pode inativar enzimas da membrana celular dos microrganismos, causando perda da atividade biológica ou integridade da membrana plasmática (Barbosa, et al, 2020). Considerando a alta solubilidade do Bio-C Sealer fresco, sua ação antibacteriana pode estar relacionada à liberação significativa de íons cálcio e hidroxila (Zordan-Bronzel, et al, 2019), capazes de inativar a endotoxina bacteriana (LPS).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…A literatura mostra que além da capacidade de induzir a biomineralização após implantação no tecido conjuntivo (Benetti, et al, 2019;Alves Silva, et al, 2020), o Bio-C Sealer tem capacidade de alcalinização atingindo pH de 10 até 21 dias (Mendes, et al, 2018;Zordan-Bronzel, et al, 2019). Sabe-se que pH superior a 9 pode inativar enzimas da membrana celular dos microrganismos, causando perda da atividade biológica ou integridade da membrana plasmática (Barbosa, et al, 2020). Considerando a alta solubilidade do Bio-C Sealer fresco, sua ação antibacteriana pode estar relacionada à liberação significativa de íons cálcio e hidroxila (Zordan-Bronzel, et al, 2019), capazes de inativar a endotoxina bacteriana (LPS).…”
Section: Resultsunclassified
“…Esse cimento foi lançado recentemente e se apresenta como uma pasta pronta para uso, e tem demonstrado favorecer a expressão de marcadores osteoblásticos e a biomineralização quando em contato com o tecido conjuntivo in vivo (Zordan-Bronzel, et al, 2019;Alves Silva, et al, 2020). Além disso, apresenta atividade antibacteriana (Barbosa, et al, 2020). Na mesma linha de cimentos prontos para uso, está o Sealer Plus BC (MK Dental Life Medical and Products, Porto Alegre, RS, Brasil) que é um material à base de dissilicato e trissilicato de cálcio nanoparticulado.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…According to the manufacturer (Angelus, Londrina -PR), Bio-C Sealer is a ready-to-use bioceramic sealing cement indicated for filling root canals. In a case study, recomposition of the periodontium new bone formation was observed after 2 years of storage (Bento & Jardim, 2019), and another study noted high antimicrobial activity, which is not only alkaline and releases calcium hydroxide, but also reduces reinfection by bacteria (Barbosa et al 2020).…”
Section: Discussionmentioning
confidence: 99%